2023
DOI: 10.1002/cctc.202201336
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Oxidative Coupling of Methane on NiFe Exsolved Perovskite Anode: Effect of Water

Abstract: Oxidative coupling of methane (OCM) can be performed electrocatalytically by utilizing solid oxide cells, which provide a readily controlled oxygen supply through dense electrolytes. La0.7Sr0.2Ni0.2Fe0.8O3 (LSNF) perovskite is an effective anode for OCM. Its surface characteristics and electrocatalytic activity can be improved by reduction and the resultant exsolution of bimetallic NiFe nanoparticles from its bulk. X‐ray diffraction (XRD) and environmental transmission electron microscopy proved that the evolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 67 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…This indicates that during the solvothermal reaction process, some of the surface oxygen atoms of Fe 3 O 4 /C were replaced by the terminal oxygen atoms of PMo 10 V 2 . 75,76 It can be observed that the hydroxyl peak of PMo 10 V 2 is located at 3430 cm −1 and the hydroxyl peak of S1 and S2 †).…”
Section: Characterization Of Morphology and Compositionmentioning
confidence: 98%
“…This indicates that during the solvothermal reaction process, some of the surface oxygen atoms of Fe 3 O 4 /C were replaced by the terminal oxygen atoms of PMo 10 V 2 . 75,76 It can be observed that the hydroxyl peak of PMo 10 V 2 is located at 3430 cm −1 and the hydroxyl peak of S1 and S2 †).…”
Section: Characterization Of Morphology and Compositionmentioning
confidence: 98%
“…The synthesized catalyst achieved only 19% ethylene selectivity in a tubular solid oxide fuel cell, as shown in Figure 18. Kim et al 123 utilized reduced as a La 0.7 Sr 0.2 Ni 0.2 Fe 0.8 O for exsolving the NiFe nanoparticles on the surface in a solid oxide cell. This modification led to the electrocatalytic performance of ∼54% C 2 + selectivity at 800 °C.…”
Section: Electrochemical Conversion Of Methanementioning
confidence: 99%
“…In addition, both regular and layered perovskites exhibit high-temperature stability and are excellent oxygen ion conductors, allowing them to meet the active site requirements for oxidative coupling of methane (OCM) and oxidative dehydrogenation of ethane (ODHE). [15][16][17][18][19][20][21][22] Thus, many of these perovskites exhibit a good catalytic performance for OCM and ODHE. Our previous research on ABO 3 perovskites and A 2 B 2 O 7 -type oxides revealed that when A-site cations are alkali metal cations (Na + or K + ) and the B-site cations are Nb 5+ ions, a 1 : 1 stoichiometric ratio of A and B can produce a regular perovskite structure (NaNbO 3 and KNbO 3 ) with orthorhombic crystal phases.…”
Section: Introductionmentioning
confidence: 99%